2010
DOI: 10.5301/jva.2010.5833
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Function Predicts Positive Arterial-Venous Fistula Remodeling in Subjects with Stage IV and V Chronic Kidney Disease

Abstract: Purpose The maturation of an arterio-venous fistula (AVF) requires remodeling of the arterial inflow and the venous outflow limbs to sustain flows sufficient to support hemodialysis. However, factors influencing remodeling of AVF are poorly understood. We hypothesized that AVF remodeling was an endothelium-dependent process. Methods This is a prospective cohort study of patients (n=25) undergoing autologous AVF formation. Brachial artery vasoreactivity studies were performed preoperatively to assess endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 18 publications
(20 reference statements)
2
29
0
Order By: Relevance
“…Owens et al [45] determined FMD among 25 CKD patients prior to AVF creation and found very similar values (5.8 ± 1.0%). Study explored the correlation between baseline FMD and subsequent change in the diameter of the artery and vein at 3 months after AVF creation and found a positive correlation.…”
Section: Endothelium Dysfunction and Avf Maturationmentioning
confidence: 76%
“…Owens et al [45] determined FMD among 25 CKD patients prior to AVF creation and found very similar values (5.8 ± 1.0%). Study explored the correlation between baseline FMD and subsequent change in the diameter of the artery and vein at 3 months after AVF creation and found a positive correlation.…”
Section: Endothelium Dysfunction and Avf Maturationmentioning
confidence: 76%
“…Recently, we examined the influence of baseline endothelial function, as measured using brachial artery flow-mediated dilation (FMD), on the subsequent remodeling of artery and vein post-AVF creation. 36 In this study, we determined that there was a positive correlation between arterial and venous enlargement post-AVF, and positive remodeling was correlated with baseline brachial FMD measured in the ipsilateral extremity. In addition, a negative relationship between diabetes and venous remodeling was observed in that cohort, and confirmed by findings in the current study.…”
Section: Discussionmentioning
confidence: 98%
“…It is important to first characterize the hemodynamics in patent accesses in order to eventually understand the negative influence of hemodynamics in failing accesses [11]. It is furthermore unlikely that effective clinical treatments for fistula maturation will be successful until a more precise characterization of fistula hemodynamics is articulated [10].…”
Section: Introductionmentioning
confidence: 99%
“…The renormalization of shear stress in the fistula vessels has been interpreted as evidence of a "mechanical homeostasis" [9]: the vessels seek to maintain a preferred mechanical state through a process of growth and remodeling. The shear-induced remodeling is widely hypothesized to be regulated in part by the vascular endothelium [10].…”
Section: Introductionmentioning
confidence: 99%